EFFECTS OF PROLONGED ADMINISTRATION OF LARGE DOSES OF ACTH ON BUFO MELANOSTICTUS TADPOLES - Ahmed, Mahmood; Hasan, Ruqaiya; Ahmad, Mansoor (Pakistan Journal of Physiology, 2018)
The present study reports the effects of different ACTH preparations, in similar and different concentrations on Bofo Melanostictus Tadpoles. Results: ACTH administration proved antagonistic to tadpole growth hormone. There seemed to be no dose-effect response when ACTH was administered in 0.02 IU/ml instead of 0.01 IU/ml. Similar ACTH concentrations with difference of manufacture showed varied biological potency. Conclusions: This perhaps indicates loss of effectiveness due to change from ACTH 1–24 to ACTH 1–18 to ACTH 1–10 in descending order.